Analisis Pemahaman Konsep Siklus Air Berbantuan Video Animasi Pada Pembelajaran IPA Kelas V SD Muhammadiyah Sidayu - Dewi Ayu Wandirah; Nataria Wahyuning Subayani; Arya Setya Nugroho (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
This study aims to analyze fifth-grade students’ understanding of the water cycle concept at SD Muhammadiyah Sidayu using animated video assistance, as well as to describe supporting and inhibiting factors, identify obstacles faced by teachers and students, explain teachers’ efforts, and examine students’ responses in science learning. The research used a descriptive qualitative method with 23 fifth-grade students as participants. Data were collected through tests, questionnaires, interviews, and observations, and analyzed using data reduction, data presentation, and conclusion drawing. Data validity was ensured through triangulation of technique, source, and time. The results indicate that students’ understanding of the water cycle concept is categorized as moderate, with an average score of 69.43. Students are able to explain the definition and stages of the water cycle through images, classify events based on similarities in processes, and distinguish between evaporation and condensation. However, they still face difficulties in explaining the relationships between processes and in providing real-life examples related to the water cycle. Supporting factors include students’ interest and learning motivation, while inhibiting factors involve differences in comprehension abilities and students’ health conditions. Teachers face obstacles such as limited audio-visual facilities, shared LCD usage, and challenges in selecting appropriate animated videos. To overcome these issues, teachers use simple explanations, emphasize key points, replay videos, provide individual guidance, and assign diagram-based projects. Students’ responses are very positive, as animated videos increase their interest, attention, motivation, and conceptual understanding.